Sistem Penunjang Keputusan Penerimaan Karyawan Baru Dengan Metode Profile Matching - Marcal Alves Da Costa (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2021)
One of the most important activities in a company or organization is the human resources. The recruitment process is a strategic stage to identify the appropriate candidates. When the recruitment process is not conducted properly, the new employees will not meet the criteria expected by the company.a decision support system application for a new employee recruitment in this research was built using the Profile Matching Method. In general, the Profile Matching Process is the process of comparing competencies between individuals and jobs or occupations to determine the suitability. The comparison was made by calculating the test scores of the recruits to get the rating scores that would serve as references in determining the decisions in the recruitment process.In applying the Profile Matching Method, determining the weight value for each aspect of the test greatly affects the final calculation of the ranking value of each employee, therefore the determination of the greatest weight value will be given to the priority aspects of the test in order to obtain the results of the selection according to the predetermined priorities according to the company's needs.Keywords: employee selection, profile matching, decision support system